Taxonomic clarifications concerning the crocodyliform genus Isisfordia - Hart, Lachlan J. (PeerJ, 2020)
Background In a recent paper, a new species of the crocodyliform genus Isisfordia was erected based on, in part, a specimen previously designated as the holotype of ‘Crocodylus (Bottosaurus)’ selaslophensis. This new species was given the name Isisfordia molnari. However, because the holotype of ‘Crocodylus (Bottosaurus)’ selaslophensis displays a unique combination of characters and does not overlap with the holotype of I. molnari, both names remain valid according to ICZN regulations. Results The present work instates Isisfordia selaslophensis comb. nov., recognising the seniority of the original specific epithet given to the specimen. The specimen is also reaffirmed as the holotype of the species. Isisfordia molnari is rediagnosed based on non-overlapping material but is potentially referable to Isisfordia selaslophensis. All other analyses, descriptions, diagnoses and conclusions stated by the original study remain valid.
Keywords: Isisfordia; Selaslophensis; Molnari; Duncani; Griman creek; Lightning ridge